THE EFFECT OF ROBUSTA COFFEE ON THE COLOR STABILITY OF THERMOPLASTIC NYLON DENTURE BASE - Darma Tsari Faizah; Sri Wahyuningsih Rais; Martha Mozartha (Universitas Baiturrahmah, 2026)
Introduction: Thermoplastic nylon is a flexible denture base material known for its excellent esthetics, making it a viable alternative for patients allergic to residual monomers or metals. However, its high water absorption rate may compromise color stability, a critical property for clinical longevity. Robusta coffee, a widely consumed beverage in South Sumatra, contains high concentrations of chromogenic agents that potentiallly induce significant staining. Aim: This study aimed to evaluate the effect of robusta coffee immersion and duration on the color stability of thermoplastic nylon denture base. Methods: This laboratory experimental study employed a pretest–posttest control group design. Thirty-two thermoplastic nylon specimens (20 × 3 mm) were divided into eight groups (n=4) and immersed in either robusta coffee or distilled water for 1, 3, 5, and 7 days. Color changes were quantified using a colorimeter. Data were analyzed using paired t-test, one-way ANOVA, and post hoc LSD tests ). Result: The paired t-test revealed significant changes in lightness (∆L) accross all groups(p<0.05. The highest mean color change (∆E) occurred in the 7-day robusta coffee immersion group (mean = 14.25), while the lowest was observed in the the 1-day distilled water group (mean = 9.68). Conclusion: Immersion in robusta coffee significantly affects the color stability of thermoplastic nylon. Furthermore, increased immersion duration correlates with a higher degree of discoloration.